TANDA DALAM KOMUNIKASI - Parapat, Nelson Halong (Jurnal Insani, 2018)
This paper provides an understanding to us that the communication process that is layman is a matter of mediocrity, in fact it is actually a terrible thing and a complex process that shows the grace of the Great Spirit for us humanity. How signs are used in human communication, reflects humans as cultured creatures and contributes to the future of Earth. Signs are things that are physical, can be perceived by our senses; sign refers to something outside the sign itself.Communication studies that specifically examine signs and meanings, and relationships between signs, are semiotics. Verbal signs in communication are signs in the form of word symbols and sequences of words (sentences) both oral and written.Nonverbal signs in communication are basically all signs that are not words (oral or written).